Does Financial Development Widen or Reduce Income Inequality? Evidence From Developed and Developing Countries - Trincy Nissi; Noer Azam Achsani; Heni Hasanah; Annisa Ramadanti (School of Business, IPB University, 2026)
Background: The financial sector has grown rapidly over the past two decades, yet income inequality remains an unresolved issue. This phenomenon raises important questions about the role of financial sector development in shaping inequality, especially given the mixed findings in existing literature depending on the proxies of financial development used.Purpose: This study aims to analyze the relationship between financial sector development and income inequality by comparing developed and developing countries, while incorporating different dimensions of financial development.Design/methodology/approach: The study uses panel data from 44 countries (both developed and developing) over the period 1980–2021. The financial sector is classified into financial institutions and financial markets, and further decomposed into three dimensions: depth, access, and efficiency. The analysis is conducted using a Fixed Effects Model (FEM) regression.Findings/Result: The results show that in developing countries, the relationship between financial development and inequality follows an inverted U-shaped pattern, where financial development initially increases inequality but eventually reduces it as financial access becomes more inclusive. In contrast, in developed countries, the relationship is positively linear, indicating that financial development tends to increase inequality due to the concentration of financial depth and access among wealthier groups.Conclusion: Financial sector development affects income inequality differently across levels of economic development. While it has the potential to reduce inequality in developing countries at later stages, it may exacerbate inequality in developed countries if financial benefits are not distributed more equitably.Originality/value (State of the art): This study contributes to the literature by providing a comparative analysis between developed and developing countries using a multidimensional approach to financial development (depth, access, and efficiency), offering deeper insights into how different aspects of the financial sector influence income inequality. Keywords:income inequality, panel data, financial development, developing countries, financial sector